2013
DOI: 10.1002/ajh.23571
|View full text |Cite
|
Sign up to set email alerts
|

Vasculopathy, inflammation, and blood flow in leg ulcers of patients with sickle cell anemia

Abstract: Chronic leg ulcers are frequent and debilitating complications of sickle cell anemia. Inadequate blood supply has been postulated to be an important factor in their occurrence and delayed healing. Little is known about their microcirculatory and histopathological changes. We evaluated the microcirculation of lower extremity ulcers with laser speckle contrast imaging and infrared thermography and obtained clinical and laboratory characteristics in 18 adults with sickle cell anemia and chronic leg ulcers. Skin b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 42 publications
2
67
2
2
Order By: Relevance
“…We have found that the active ulcer and peri-ulcer area have higher blood flow than distant, non-ulcerated areas of the leg, are characterized histopathologically by venostasis, inflammation, and vasculopathy, with activated endothelium and evidence of thrombosis/recanalization (Figs. 3 and 4) [44]. Hypoxia is well known to induce angiogenesis, therefore it is conceivable that chronic hypoxia in ulcerated skin leads to increase in capillary proliferation and recruitment, with higher measured blood flow.…”
Section: Pathophysiologymentioning
confidence: 99%
See 4 more Smart Citations
“…We have found that the active ulcer and peri-ulcer area have higher blood flow than distant, non-ulcerated areas of the leg, are characterized histopathologically by venostasis, inflammation, and vasculopathy, with activated endothelium and evidence of thrombosis/recanalization (Figs. 3 and 4) [44]. Hypoxia is well known to induce angiogenesis, therefore it is conceivable that chronic hypoxia in ulcerated skin leads to increase in capillary proliferation and recruitment, with higher measured blood flow.…”
Section: Pathophysiologymentioning
confidence: 99%
“…3, panel C), but whether this leads to an effective increase in perfusion and oxygen delivery needs to be determined by further analysis. A possible role for in situ thrombosis is supported by plasma markers of thrombophilia [44][45][46] and 44% prevalence of venous thromboembolism in SCD ulcer patients [44], and by results of a pilot study of antithrombin use in treatment of SCD leg ulcer [47]. Oxidative stress plays an important pathogenic role in the development of SCD related complications, and patients with glutathione S-transferase polymorphism (GSTM1 and GSTT1 null phenotype) have recently been shown to have a high risk of developing ulcers [48].…”
Section: Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations